Competition in the acquisition market and acquirers' long‐run performance. (5th February 2019) - Shams, Syed; Gunasekarage, Abeyratna
Abstract: Using a large sample of completed acquisition deals in Australia, this study examines the influence of competition in the acquisition market on the long‐run operating performance of acquirers of private target firms in comparison to that of acquirers of public target firms. We find that, in contrast to acquirers targeting private firms, those targeting public firms improve their performance in the long run through competition‐induced bids. However, in a competitive takeover market, public target acquirers experience significant declines in performance when acquiring targets that are labelled high performers. Additionally, public target acquirers report improved performance when acquiring a significant ownership stake in target firms.